Nevarna razmerja družbe znanja - Autor, Sabina (Šolsko polje, 2013)
The article attempts to highlight concepts such as knowledge society, lifelong learning, competencies, etc.., which are central in today's political discourse as well as the professional arena. Exposed concepts are discussed inlight of changes in the very concept of knowledge as a result of their introduction to the field of education and science as well as in other areas of society. In addition, these changes exist within the paradigm of society and within the very substance of its fields. Knowledge transferred from its traditionally inherent fields of society to the economic field enables school, education, science, etc. to themselves become also agents of neoliberalism, not just merely a place for the exercise of neo-liberal ideas.
Keywords: knowledge; znanje; knowledge-based society; neoliberalizem; družba znanja; lifelong learning; vseživljenjsko učenje; competencies; vzgoja in izobraževanje; neoliberalism; education